America's worst charities: The effect of bad press on philanthropic giving behavior. Issue 1 (19th April 2018) - Jones, Jennifer A.; Cantrell, Randall A.; Lindsey, Angela B.
Abstract : Negative media stories about nonprofits can potentially lead to decreased financial donations. We used agenda setting theory to study donors' perceptions of what could arguably be called one of the most negative nonprofit media stories in recent times: the 2013 Tampa Bay Times report titled "America's worst charities." This news story identified and ranked America's 50 worst charities based on solicitation (i.e., fundraising) costs and was investigated further by CNN. We surveyed 655 individuals in August 2016 and found that approximately 3 years since the story had aired, 278 (42.4%) of the sample still remembered the news story, and the majority of them reported that it negatively influenced their thinking (63%) and philanthropic donation behavior (62%). These findings have implications for nonprofit media relations and fundraising.